Internal fights over resources: The effect of power struggles on team innovation - Kang, Sung Mo (Frontiers in Psychology, 2022)
Power hierarchy is a recently growing topic among scholars. Although the previous literature has emphasized the importance of understanding power hierarchy in teams and demonstrated the negative consequences of power struggles among team members in team performance, it neglected to explore how power struggles impact other team functioning and outcomes. Drawing on social information processing theory and the team learning behavior model discussed, this study proposes that power struggles send aggressive social information to team members, and such social information negatively influences team learning. Social information emitted by power struggles undermines psychological safety and creates hostility and interpersonal tensions, which reduce team members’ providing new ideas and information sharing. In addition, this study proposes a positive relationship between team learning and team innovation since team learning provides two key conditions (i.e., active knowledge integration and appropriate team climate) for successful team innovation. Lastly, this study suggests the mediating role of team learning between power struggles and team innovation. Using a sample of 99 teams from two organizations in Korea, this study tested the proposed model. In sum, this study found that (1) power struggles are negatively related to team learning, (2) team learning is positively related to team innovation, and (3) team learning mediates the relationship between power struggles and team learning.